Serum anti‐GM2 and anti‐GalNAc‐GD1a IgG antibodies are biomarkers for acute canine polyradiculoneuritis. (17th November 2021) - Halstead, S. K.; Gourlay, D. S.; Penderis, J.; Bianchi, E.; Dondi, M.; Wessmann, A.; Musteata, M.; Le Chevoir, M.; Martinez‐Anton, L.; Bhatti, S. F. M.; Volk, H.; Mateo, I.; et al.
Abstract : Objectives: A previous single‐country pilot study indicated serum anti‐GM2 and anti‐GA1 anti‐glycolipid antibodies as potential biomarkers for acute canine polyradiculoneuritis. This study aims to validate these findings in a large geographically heterogenous cohort. Materials and Methods: Sera from 175 dogs clinically diagnosed with acute canine polyradiculoneuritis, 112 dogs with other peripheral nerve, cranial nerve or neuromuscular disorders and 226 neurologically normal dogs were screened for anti‐glycolipid antibodies against 11 common glycolipid targets to determine the immunoglobulin G anti‐glycolipid antibodies with the highest combined sensitivity and specificity for acute canine polyradiculoneuritis. Results: Anti‐GM2 anti‐glycolipid antibodies reached the highest combined sensitivity and specificity (sensitivity: 65.1%, 95% confidence interval 57.6 to 72.2%; specificity: 90.2%, 95% confidence interval 83.1 to 95.0%), followed by anti‐GalNAc‐GD1a anti‐glycolipid antibodies (sensitivity: 61.7%, 95% confidence interval 54.1 to 68.9%; specificity: 89.3%, 95% confidence interval 82.0 to 94.3%) and these anti‐glycolipid antibodies were frequently present concomitantly. Anti‐GA1 anti‐glycolipid antibodies were detected in both acute canine polyradiculoneuritis and control animals. Both for anti‐GM2 and anti‐GalNAc‐GD1a anti‐glycolipid antibodies, sex was found a significantly associated factor with a female to male odds ratio of 2.55 (1.27 to 5.31) and 3.00 (1.22 to 7.89), respectively. Anti‐GalNAc‐GD1a anti‐glycolipid antibodies were more commonly observed in dogs unable to walk (OR 4.56, 1.56 to 14.87). Clinical Significance: Anti‐GM2 and anti‐GalNAc‐GD1a immunoglobulin G anti‐glycolipid antibodies represent serum biomarkers for acute canine polyradiculoneuritis.